Finland's Continuation War (1941-1944): War of Aggression or Defence? War of Alliance or Separate War? : Analyzed from the International - Especially Legal - Perspective - Hannikainen, Lauri (Baltic Yearbook of International Law Online, 2021)
Tämä on ensimmäinen kansainvälisoikeudellinen analyysi jatkosodan oikeudellisesta luonteesta. Oliko se kansainvälisen oikeuden kieltämä hyökkäyssota vai sallima puolustussota? Oliko se Liittolaissota Saksan kanssa vai Suomen erillissota Neuvostoliittoa vastaan? Johtopäätökseni: syksyllä 1941 Suomi liittyi Saksan laittomaan hyökkäyssotaan Neuvostoliittoon ja Suomi valtasi Neuvostoliitolle kuuluneen Itä-Karjalan. Vuoden 1942 alkuun mennessä Suomi katsoi saavuttaneensa sen, mitä se tavoitteli, ja sen sodankäynti muuttui rintamasodaksi ja svuodesta 1943 lähtien puolustussodaksi. Liitto Saksan kanssa kävi heikommaksi, mutta Saksalta saamansa avun takia Suomi pysyi muodollisesti Saksan liittolaisena aina rauhan solmimiseen saakka eli syyskuuhun 1944. In September 1939, after having included a secret protocol on spheres of influence in the so-called Molotov- Ribbentrop Pact, Germany and the Soviet Union invaded Poland and divided it between themselves. It was not long before the Soviet Union approached Finland by proposing exchanges of certain territories: ‘in our national interest we want to have from you certain territories and offer in exchange territories twice as large but in less crucial areas’. Finland, suspicious of Soviet motives, refused – the outcome was the Soviet war of aggression against Finland by the name of the Winter War in 1939–1940. The Soviet Union won this war and compelled Finland to cede several territories – about 10 per cent of Finland’s area. After the Winter War, Finland sought protection from Germany against the Soviet Union and decided to rely on Germany. After Germany attacked the Soviet Union in June 1941, Finland joined the German war effort in the so-called Continuation War and reoccupied the territories lost in the Winter War. Finnish forces did not stop at the old border but occupied Eastern (Soviet) Karelia with a desire eventually to annex it. By that measure, Finland joined as Germany’s ally in its war of aggression against the Soviet Union in violation of international law. In ...